Aktivitas ANtibakteri Fraksi Daun Kakao (Theobroma cacao L.) terhadap Bakteri Staphylococcus aureus Secara In Vitro: Antibacterial Activity of Cocoa Leaf Fraction (Theobroma cacao L.) against Staphylococcus aureus Bacteria by In Vitro - Noviana Mandhaki; Choirul Huda; Amalia Eka Putri (Jurnal Sains dan Kesehatan, 2021)
Cacao are a plantation commodity in Indonesia. Most of the cacao plant is cacao leaves. One of the utilization of cacao leaves by the community is as compost, but has not been utilized by the community as a raw material of traditional medicine. Based on research, cacao leaves contain secondary metabolite compounds that can be used as an antibacterial against Staphylococcus aureus bacteria that often cause infection in humans. The purpose of this study was to find out the activity of ethanol fraction, dichloromethane, and n-hexane from cacao leaf extract as an antibacterial against Staphylococcus aureus ATCC 25923. This study used extraction methods of maceration and fractionation using ethanol solvents, dichloromethane, and n-hexane. Test the antibacterial activity of cacao leaf fraction using disc diffusion method with a concentration series of 10%, 20%, and 30%. The results showed that ethanol and dichloromethane fractions had antibacterial activity.